2019
DOI: 10.1007/s42452-019-1055-6
|View full text |Cite
|
Sign up to set email alerts
|

CO2 adsorption in hydrochar produced from waste biomass

Abstract: Sugar and ethanol plants produce a large amount of sugarcane bagasse. Such biomass can be the raw material for the production of an adsorbent to uptake CO 2. Thus, this work aimed to evaluate the hydrocarbonization of sugarcane bagasse and to study its use as a CO 2 adsorbent from a simulated flue gas. The temperature of the hydrothermal carbonization (HC) was set at 220 °C, while the operating time ranged from 12 to 48 h. Through the SEM-EDS analysis, the 48-h sample (HC48) was selected for chemical activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…On the other hand, by activating the hydrochars obtained in the basic environment, the CO2 sorption capacity can be increased approximately 9 times. The CO2 adsorption capacities of activated HCs is similar to that reported in other studies [23], [24].…”
Section: Environmental and Climate Technologies _____________________...supporting
confidence: 88%
“…On the other hand, by activating the hydrochars obtained in the basic environment, the CO2 sorption capacity can be increased approximately 9 times. The CO2 adsorption capacities of activated HCs is similar to that reported in other studies [23], [24].…”
Section: Environmental and Climate Technologies _____________________...supporting
confidence: 88%
“…The appropriate HTC parameters for rambutan peel biomass at 170 °C and 90 min of retention time was reported for CO 2 capture [17]. A study by Fagnani et al [18] on CO 2 adsorption using hydrochar from sugarcane bagasse biomass found that at a HTC temperature of 220 °C the optimal retention time was 48 h. Other researches [6,10,19] demonstrated that the optimal HTC parameters for CO 2 capture were strongly dependent on the type of biomass feedstock. In this study, PPW-HC showed the highest CO 2 capture at 200 °C and 2 h, with 5 °C min -1 heating rate.…”
Section: Effects Of Hydrothermal Carbonizationmentioning
confidence: 99%
“…No reator foram adicionados 3,0 g de retalhos e 80 mL de água destilada. Tal sistema foi submetido à carbonização com duração de 6, 8, 10 ou 12 horas a 220 ºC [24]. Logo após o referido processo, os hidrocarvões resultantes foram secos em estufa por 5 horas a 105 ºC.…”
Section: Síntese Do Hidrocarvão De Resíduos Têxteisunclassified